x+3=-5x+27

Simple and best practice solution for x+3=-5x+27 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+3=-5x+27 equation:


Simplifying
x + 3 = -5x + 27

Reorder the terms:
3 + x = -5x + 27

Reorder the terms:
3 + x = 27 + -5x

Solving
3 + x = 27 + -5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5x' to each side of the equation.
3 + x + 5x = 27 + -5x + 5x

Combine like terms: x + 5x = 6x
3 + 6x = 27 + -5x + 5x

Combine like terms: -5x + 5x = 0
3 + 6x = 27 + 0
3 + 6x = 27

Add '-3' to each side of the equation.
3 + -3 + 6x = 27 + -3

Combine like terms: 3 + -3 = 0
0 + 6x = 27 + -3
6x = 27 + -3

Combine like terms: 27 + -3 = 24
6x = 24

Divide each side by '6'.
x = 4

Simplifying
x = 4

See similar equations:

| m^2+17m+30=0 | | 9x+16=5x-12 | | 19=6p+1 | | y=(x^2-6*x^2+9*x) | | 6x+19=-x-16 | | m^2-13m+36=0 | | -6x-13=-3x-19 | | x-9y=-85 | | 4x-14=-3x+21 | | 47-(y-4)=-20 | | 9x+4=27 | | 8x-3=-5x-18 | | 6w-5x-4w-2x= | | 3x-4=44+x | | 67=11+1 | | 9+3x=12+6x | | 2376=18*11h | | 79x+99y=26000 | | -7(a+1)=-11(a+1) | | 2b+10(8+3b)=12(b+10) | | 6-4=4x+10 | | (xy+x^2y^3)dy=dx | | 19+3r=-8+3(3-5r) | | 2-(-8-1)=30-8m | | -9+v=8(5v-6) | | 8(-0-3)-8p=-7p+30 | | 3x+8=8(9x-9) | | -5n-2=-7(7n-6) | | -3(-1+5k)=-8k+24 | | 4.33=6.66x | | -7(x-1)=-38+8x | | 27x^2+12x=0 |

Equations solver categories